Stereoselective synthesis of (−)-synargentolide B. Issue 3 (17th January 2018) - Gao, Yangguang; Liu, Jun; Qiao, Junfei; Liu, Yinxin; He, Peng; Du, Yuguo
Graphical abstract: Highlights: A concise synthesis of unnatural synargentolide B has been accomplished in 10 steps. Abundantly availablel -arabinose andd -ethyl lactate was used as chiral template. The key steps include olefin CM reaction and one-pot deprotection-lactonization. Abstract: A convergent, enantioselective total synthesis of (−)-synargentolide-B has been accomplished from readily availablel -arabinose andd -ethyl lactate by a 10-step sequence involving Still-Gennari olefination, one-pot acidic deprotection/lactonization and olefin cross-metathesis reaction as the key step.